Perinatal Breathing Patterns and Survival in Mice Born Prematurely and at Term - Ramirez, Sanja C.; Koschnitzky, Jenna E.; Youngquist, Tiffany M.; Baertsch, Nathan A.; Smith, Charles V.; Ramirez, Jan-Marino (Frontiers in Physiology, 2019)
Infants born prematurely, often associated with maternal infection, frequently exhibit breathing instabilities that require resuscitation. We hypothesized that breathing patterns during the first hour of life would be predictive of survival in an animal model of prematurity. Using plethysomography, we measured breathing patterns during the first hour after birth in mice born at term (Term 19.5), delivered prematurely on gestational day 18.5 following administration of low dose lipopolysaccharide (LPS; 0.14mg/kg) to pregnant dams (LPS 18.5), or delivered on gestational day 18.7 or 17.5 by caesarian section (C-S 18.5 and C-S 17.5, respectively) . Our experimental approach allowed us to dissociate effects caused by inflammation, from effects due to premature birth in the absence of an inflammatory response. C-S 17.5 mice did not survive, whereas mortality was not increased in C-S 18.5 mice. However, in premature pups born at the same gestational age (day 18.5) in response to maternal LPS injection, mortality was significantly increased. Overall, mice that survived had higher birth weights and showed eupneic or gasping activity that was able to transition to normal breathing. Some mice also exhibited a “saw-tooth” breathing pattern that was able to transition into eupnea during the first hour of life. In contrast, mice that did not survive showed distinct, large amplitude, long-lasting breaths that occurred at low frequency and did not transition into eupnea. This breathing pattern was only observed during the first hour of life and was more prevalent in LPS 18.5 and C-S 18.5 mice. Indeed, breath tidal volumes were higher in inflammation-induced premature pups than in pups delivered via C-section at equivalent gestational ages, whereas breathing frequencies were low in both LPS-induced and C-section-induced premature pups. We conclude that a breathing pattern characterized by low frequency and large tidal volume is a predictor for the failure to survive, and that these characteristics are more often seen when prematurity occurs in the context of maternal inflammation. Further insights into the mechanisms that generate these breathing patterns and how they transition to normal breathing may facilitate development of novel strategies to manage premature birth in humans.